Comparison of the precision of two electronic apical locators in teeth with simulated perforations - Astocaza Reátegui, Teresa Flora (2021)
Objective: The purpose of the study was to compare the precision of the Propex Pixi and Raypex 6 electronic apical locators in determining the working length of teeth with simulated perforations at different levels of the root canal. Materials and Methods: 36 uniradicular lower premolars were used with a canal randomly divided into three groups of 12 teeth each. In the first group two simulated perforations were made at the middle and apical level. In the second group a simulated cervical perforation was made, and in the third group a simulated perforation was performed at the apical level. Two electronic apical locators Propex Pixi and Raypex 6 were used, and the real length of the canal was measured with a digital Vernier caliper. Descriptive and inferential statistics were applied with the Friedman test at a confidence level of 95%. Results: When comparing the precision of the lengths obtained by the Propex Pixi and Raypex 6 apical electronic locators, statistically significant differences were found in the real length of the canal (p= 0.006) between simulated perforation of lower premolars at the cervical (p<0.001) and the apical level (p=0.008), Conclusion: The Propex Pixi apical electronic locator (Dentsply Maillefer - Germany) presented greater precision in the determination of the real canal length in teeth with simulated perforations at different levels of the root canal.